2017
DOI: 10.1037/rmh0000069
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in breast cancer survivors: Sources of support in rural and non-rural areas.

Abstract: The aim of this literature review is to summarize the relationship between breast cancer survival and posttraumatic growth (PTG). Because of the many inconsistencies found in the literature related to variables that foster PTG in breast cancer survivors, the relationship needed to be clarified. Breast cancer is often viewed as a traumatic experience, and although 1 might expect only negative effects, studies show that breast cancer survivors often experience PTG, which can manifest in many forms and is influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(110 reference statements)
2
5
0
Order By: Relevance
“…The average mean values of BCSv staying in villages and small towns reported less FCR when compared to those who were staying in metropolitan cities, which falls in line with the results of LeBarre & Riding‐Malon 20 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The average mean values of BCSv staying in villages and small towns reported less FCR when compared to those who were staying in metropolitan cities, which falls in line with the results of LeBarre & Riding‐Malon 20 …”
Section: Discussionsupporting
confidence: 86%
“…[2][3][4][5][6][7] The average mean values of BCSv staying in villages and small towns reported less FCR when compared to those who were staying in metropolitan cities, which falls in line with the results of LeBarre & Riding-Malon. 20 The mean scores suggest that less-educated BCSv were experiencing low FCR, which is the same as the study results of Custers et al 10 in which higher educated breast cancer survivors reported greater FCR.…”
Section: Discussionsupporting
confidence: 82%
“…7 However, in other groups of cancer survivors results have been mixed, reporting both improvements and declines in mental health longitudinally posttreatment. 38,39 These inconsistencies support the need for further research in this area and the consideration of rural/urban residence as a variable in these findings. Continued monitoring of mental health symptoms in rural NHL survivors is still warranted, as well as supportive treatment to continue to bolster mental health wellness in NHL survivors.…”
Section: Discussionmentioning
confidence: 89%
“…It appears that the role of spiritual support, in comparison to other types of support, may be especially valuable because a life-threatening disease can trigger a crisis of values and inspire questions about the sense of life and death (Levy et al, 1992). Spiritual support could be a source of strength and foster growth more effectively than nonreligious forms of social support and may be more valuable, especially to those dealing with health concerns such as breast cancer (LeBarre and Riding-Malon, 2017).…”
mentioning
confidence: 99%